Avifaunae columbiensis notulae-ii: seis nuevas aves para colombia y apuntamiento sobre sesenta especies y subespecies registradas anteriormente (1967)
Sixty six species aud subspecies are treated with the following results: six are new for the Colombian ornis: Forpus passerinus crassirostris Nonnula rubecula cineracea Fornarius minor Certhiaxis mustelina Elaenia s. spectabilis Turdus fumigatus hauxwelli Some citations are range extensions especially to the extreme southeastern region of the Comisaría del Amazonas. Areas of intergradation of particular subspecies are determined. Precise localities of Cathertes melambrotus are added and also chromatic characteristic of the bare parts of this Greater Yellow-headed Vulture. The presence of Coragyps atratus foetens in Colombia is confirmed. The immature plumage of Grallaria quitensis alticola is described. The capture of Larus atricilla in the Lago de Tota (Boyacá) is interesting.